Fața nevăzută a Elenei Drăgănescu - Simona Galațchi (Revista de Istorie și Teorie Literară)
This article sets out to reveal unseen, so far, aspects of a highly appreciated character of Hortensia Papadat-Bengescu, Elena Drăgănescu. The unexpected angles of this character are brought up to the surface by the means of the psychoanalytical method applied on the facts that appear all along the Hallipa’s Cycle novels and in the novel The Stranger. The article is structured in two sections: the first section introduces readers to the story of Elena Drăgănescu such as it is perceived by other characters and by the writer herself; the second section diagnoses this character and draws conclusions on her psychological complexes, on her ranging in the typology of C. G. Jung and Otto Rank while analyzing her drives based on Sigmund Freud’s, Alfred Adler’s and Jacques Lacan’s psychoanalytical visions.